2023
DOI: 10.1021/acsestengg.3c00009
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Graphdiyne Nanotubes for Metal-Free Activation of Peroxymonosulfate and Enhanced Degradation of Recalcitrant Heterocyclic Contaminants

Abstract: Pollution removal via peroxymonosulfate (PMS)-mediated advanced oxidation processes provides an effective approach for water remediation. Although numerous carbon allotropes have been applied in PMS activation, the application of graphdiyne-based catalysts has been practically unexplored in this process despite their excellent electronic properties. In this study, the first instance of exploiting N-doped graphdiyne nanotubes (NGNTs) for metal-free PMS activation is presented to remove recalcitrant heterocyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
(130 reference statements)
0
5
0
Order By: Relevance
“…Metal-involved catalysts have the potential to produce both radical and nonradical species. , Graphitic carbon-based materials tend to mediate electron transfer, resulting in reaction progression via nonradical pathways . Nitrogen doping is commonly considered to be an effective method to optimize the electron configuration of carbonaceous materials, thereby enhancing their catalytic ability to promote 1 O 2 generation from PS. , N-doped biochar (NBC) is the most commonly utilized method for carbon-based catalyst modification, with the active sites on the surface of NBC significantly promoting the generation of radical and nonradical species, further accelerating the degradation of pollutants . It has been shown that NBCs give better catalytic performance for tetracycline degradation of persulfate compared to that of typical graphitic carbon (graphite powder, graphene oxide and multiwalled carbon nanotubes) .…”
Section: Introductionmentioning
confidence: 99%
“…Metal-involved catalysts have the potential to produce both radical and nonradical species. , Graphitic carbon-based materials tend to mediate electron transfer, resulting in reaction progression via nonradical pathways . Nitrogen doping is commonly considered to be an effective method to optimize the electron configuration of carbonaceous materials, thereby enhancing their catalytic ability to promote 1 O 2 generation from PS. , N-doped biochar (NBC) is the most commonly utilized method for carbon-based catalyst modification, with the active sites on the surface of NBC significantly promoting the generation of radical and nonradical species, further accelerating the degradation of pollutants . It has been shown that NBCs give better catalytic performance for tetracycline degradation of persulfate compared to that of typical graphitic carbon (graphite powder, graphene oxide and multiwalled carbon nanotubes) .…”
Section: Introductionmentioning
confidence: 99%
“…[12] PS-AOPs are generally derived by activating peroxymonosulfate (PMS) or peroxydisulfate (PDS) with additional energy sources or catalysts, such as heat, [15] photoexcitation, [16] microwave, [17,18] ultrasound, [19,20] electrical field energies, [21] heterogenous catalysts (i.e., transition metal oxide, metal-free material, and single-atom catalyst). [13,19,[22][23][24][25][26] Although a multitude of studies have exhibited the high efficiency of catalyst activation systems in laboratory conditions, they concurrently confront formidable challenges that bear implications for practical applications. These encompass the requirement for mitigating secondary contamination factors, notably toxic ions and dispersed nanoparticles, and augmenting persulfate (PS) utilization efficiency, which, as it currently stands, demands a PS dose roughly 100 times greater than the organic concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies regarding SACs present the substrates based on sp 2 -hybridized carbon materials, e.g., nanotubes and graphene. However, sp-hybridized carbon-based substrates have rarely been studied in the synthesis of SACs. Graphdiyne and γ-graphyne, as artificial π-conjugated carbon allotropes, possess a 2D framework with sp 2 - and sp-hybridized carbon atoms. Compared to sp 2 -hybridized carbon frameworks, the structural linearity of the carbon–carbon triple bond (sp-hybridized carbons) avoids the fluctuation arising from cis – trans isomerization and has small steric demands. , Importantly, the absence of hexagonal symmetry and two self-doped nonequivalent distorted Dirac cones endow graphdiyne and γ-graphyne with electronic conduction properties superior to those of sp 2 -hybridized carbons. , Previous studies also show that graphdiyne substrates are more appropriate for nitrogen-doping modification compared with graphene series materials . The abundant nitrogen sites on carbonaceous substrates were verified in previous studies to anchor atomically dispersed metal sites .…”
Section: Introductionmentioning
confidence: 99%